1995
DOI: 10.1161/01.cir.91.5.1432
|View full text |Cite
|
Sign up to set email alerts
|

Non–Insulin-Dependent Diabetes Mellitus and Fasting Glucose and Insulin Concentrations Are Associated With Arterial Stiffness Indexes

Abstract: Our findings are compatible with the view that persons with NIDDM or borderline glucose intolerance have stiffer arteries than their counterparts with normal glucose tolerance and that the decreased elasticity is independent of artery wall thickness. The joint effect of elevated glucose, insulin, and triglycerides can have a considerable impact on arterial stiffness and play an important role in the early pathophysiology of macrovascular disease in NIDDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
343
3
21

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 525 publications
(394 citation statements)
references
References 71 publications
27
343
3
21
Order By: Relevance
“…7 Increased aortic PWV has been described by both Wahlqvist 26 and Lehman 27 in otherwise healthy subjects with type 2 diabetes. Salomaa 28 and Emoto 29 have also reported increased carotid artery stiffness in this patient group. Furthermore, in the ARIC study, carotid artery stiffness was positively correlated with serum glucose concentration.…”
Section: Arterial Stiffness and Type 2 Diabetes Mellitussupporting
confidence: 63%
See 2 more Smart Citations
“…7 Increased aortic PWV has been described by both Wahlqvist 26 and Lehman 27 in otherwise healthy subjects with type 2 diabetes. Salomaa 28 and Emoto 29 have also reported increased carotid artery stiffness in this patient group. Furthermore, in the ARIC study, carotid artery stiffness was positively correlated with serum glucose concentration.…”
Section: Arterial Stiffness and Type 2 Diabetes Mellitussupporting
confidence: 63%
“…Furthermore, in the ARIC study, carotid artery stiffness was positively correlated with serum glucose concentration. 28 Emoto reported an inverse correlation between stiffness and insulin sensitivity, and a positive correlation between stiffness and duration of diabetes. Abnormalities of the brachial pressure waveform, consistent with increased peripheral arterial stiffness, can also be detected early in the course of type 2 diabetes before complications of the disease become apparent.…”
Section: Arterial Stiffness and Type 2 Diabetes Mellitusmentioning
confidence: 98%
See 1 more Smart Citation
“…Nevertheless, most of the study subjects had type II diabetes or IGT, and previous studies have suggested that such subjects may have stiffer Blood pressure and atherosclerotic plaques U Rajala et al vessels than subjects with abnormal glucose tolerance. 33 Except for high SBP, high MBP was also associated with plaques in this study population. Apart from BP, male gender 5,12,28,30 and smoking [13][14]30 are well-established risk factors for atheromatous plaques.…”
Section: Discussionmentioning
confidence: 59%
“…Assuming that the change in volume is due to a change in arterial crosssection rather than a change in arterial length, crosssectional compliance (CC) and distensibility (DC), defined as absolute respectively relative changes in arterial cross-sectional area divided by the change in arterial pressure, are simplified representatives of compliance and distensibility. 1 An unfavourable change in dynamic arterial wall properties of various arteries is found in populations with cardiovascular risk factors such as hypertension, 2,3 smoking, 4 diabetes mellitus 5 and in patients with cerebrovascular disease. 6 A low CC is associated with a high pulse pressure and a high end-systolic wall stress, both involved in the development of carCorrespondence: F van den Berkmortel, Department of Medicine, Division of General Internal Medicine, University Hospital Nijmegen, P.O.…”
Section: Introductionmentioning
confidence: 99%